Time-Restricted Inquiry-Based Learning Promotes Active Student Engagement in Undergraduate Zoology Laboratory - Thitinun Sumranwanich (American Society for Microbiology, 2019)
Organizing a zoology laboratory for an undergraduate course is often a challenge, particularly in a limited-resource setting, due to the vast variety of topics to cover and the limited numbers of preserved specimens and permanent slides. In zoology, the class structure generally takes the form of a lecture demonstration followed by sample exhibition stations. This setting often fails to actively engage the majority of students in exploring the specimens. Here we propose an alternative organization of a zoology class lab format comprised of short guided-inquiry, time-restricted lab stations, and a freely structured follow-up project intended to increase attention and conceptual understanding of the lab topic. The lab is designed in two parts: a 10-minute in-class rotation portion, where small groups of students take turns investigating specimens following an instructor demonstration, and an after-class group assignment. We implemented the strategy for two years, and it is clear that our approach significantly increased students’ active engagement in the class. The time-restricted scheme ensures all students participate despite limited resources, while the guided instructions keep the students focused on the topic. Furthermore, the team assignment portion, in particular the media creation aspect, promoted teamwork among group members.